Histologic and molecular features in pathologic human menisci from knees with and without osteoarthritis. Issue 2 (19th April 2021) - Monibi, Farrah A.; Pannellini, Tania; Otero, Miguel; Warren, Russell F.; Rodeo, Scott A.
Abstract: The objective of this study was to evaluate histologic and molecular features of meniscus degeneration in cohorts of patients with and without osteoarthritis (OA) of the knee. Menisci were obtained from patients undergoing total knee arthroplasty for OA (TKA) or arthroscopic partial meniscectomy (APM) for a torn knee meniscus. Degenerative meniscal tears were among the most common tear type in the APM group based on the pattern. Using an integrative workflow for molecular evaluation of formalin‐fixed and paraffin‐embedded tissues, human menisci underwent blinded histologic evaluation and NanoString gene expression analyses. Histology revealed increased proteoglycan content in TKA menisci compared to APM menisci, but otherwise no significant differences in the total pathology score or sub‐scores between patients based on age or cohort. NanoString analyses revealed differential expression of genes primarily associated with the PI3K‐AKT signaling pathway, cell cycle, and apoptosis. These data provide new insights into histological and molecular features of meniscus degeneration in patients with and without knee OA. Histologic assessment of menisci showed similar severity of overall degeneration between cohorts, but there were differences at the molecular level. The dysregulated pathways identified in this study could contribute to early‐onset meniscus degeneration, or to a predisposition to meniscus tears and subsequent knee OA. Further studies that validate genes and pathways uncovered in this study will allow us to evaluate novel approaches to assess and treat meniscal degeneration.